Implementation of Quality Control in the Trucking Division of PT Mitra Dua Mandiri Logistic - Hilmy Ar Razy; Nursya'bani Purnama (PT SOLUSI EDUKASI BERDIKARI, 2024)
Import export trade plays an important role in the development of the world economy, including Indonesia. The presence of the Customs Service Management Company (PPJK) is to connecting customs and excise and consumers which can facilitate the process of import export trade traffic. One of the important processes in shipping goods is the trucking system which is useful for making deliveries with a fleet provided by PT Mitra Dua Mandiri Logistic. Trucking is important in the company because it plays an important role and is directly related to consumers. The existence of a quality control process in the trucking system can help the company to continue to maintain good trucking operations. This study aims to determine the trucking system in facilitating the shipping process of PT Mitra Dua Mandiri Logistic. This study uses a qualitative method with sources of literature studies, documentation, observation, and interviews. The results of this study prove that the trucking work system at PT Mitra Dua Mandiri Logistic has been running well, but there are still obstacles in operational activities.